Prediction of injection-moulded flax fibre reinforced polypropylene tensile properties through a micro-morphology analysis. (January 2015) - Lafranche, Eric; Oliveira, Vânia M; Martins, Carla I; Krawczak, Patricia
Micromechanical models usually applied to predict the mechanical properties of short glass fibre reinforced composites were used to evaluate the Young's modulus and tensile strength of flax fibre reinforced polypropylene. Due to lack of accuracy between the experimental results and the existing models, a new adjustment to the Kelly-Tyson model was proposed. The changes were based on the understanding of the microstructure obtained in polypropylene/flax fibre composites produced by injection moulding with different flax fibre content. The mechanical properties were interpreted based on real fibre loading, fibre orientation, fibre dimension distribution and morphology of the composites. Lack of fibre/matrix adhesion, strong fibre damage and changes on the crystallization behaviour of polypropylene in the presence of flax fibres affect the mechanical strength, stiffness and elongation of the composites. The Kelly-Tyson's model used for tensile strength prediction was modified to take into consideration the fibre property variability due to the large distribution of fibre shape ratio induced by the process. Finally, matrix modulus has been adjusted to take into account the change of crystallinity with fibre content. A better description of the mechanical properties is obtained using the proposed approach, resulting indeed in an excellent approximation to the modulus of the composite.